2021
DOI: 10.1111/imcb.12443
|View full text |Cite
|
Sign up to set email alerts
|

CD5 levels reveal distinct basal T‐cell receptor signals in T cells from non‐obese diabetic mice

Abstract: Type 1 diabetes in non-obese diabetic (NOD) mice occurs when autoreactive T cells eliminate insulin producing pancreatic b cells. While extensively studied in T-cell receptor (TCR) transgenic mice, the contribution of alterations in thymic selection to the polyclonal T-cell pool in NOD mice is not yet resolved. The magnitude of signals downstream of TCR engagement with self-peptide directs the development of a functional T-cell pool, in part by ensuring tolerance to self. TCR interactions with self-peptide are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…It is tempting to speculate that heterogeneity in sensitivity to anti-PD-1 exists among anergic T cell populations and that this is imprinted based on the strength of TCR signal induced during anergy induction. Indeed, accumulating evidence implicates rather low affinity T cells in the development of autoimmune pathologies illustrating the importance of considering the entire spectrum of TCR affinity to self in terms of the efficiency and ‘quality’ of tolerance induction [ 4 , 22 , 52 , 135 ].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is tempting to speculate that heterogeneity in sensitivity to anti-PD-1 exists among anergic T cell populations and that this is imprinted based on the strength of TCR signal induced during anergy induction. Indeed, accumulating evidence implicates rather low affinity T cells in the development of autoimmune pathologies illustrating the importance of considering the entire spectrum of TCR affinity to self in terms of the efficiency and ‘quality’ of tolerance induction [ 4 , 22 , 52 , 135 ].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…CD4 + T cells with relatively higher basal self-reactivity predominate during acute antigen challenge and are preferentially recruited into the memory T cell pool [ 14 , 19 , 20 ]. In addition, there is evidence of T helper biases among CD4 + T cells with relatively high versus low affinity for self-peptide [ 19 , 20 , 21 , 22 ]. While some of these characteristics might be continually influenced by tonic signals (interactions between naïve T cells and self-pMHC that are necessary for their survival) in secondary lymphoid organs, there is evidence that some functional biases might be imprinted during their differentiation into mature T cells in the thymus based on the strength of positive selection signals [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 , 19 T cells are necessary and sufficient for autoimmune diabetes onset and progression, 20 , 21 , 22 and it has been suggested that defects in central T-cell tolerance in NOD mice contribute to the development of autoimmune diabetes. 23 , 24 , 25 , 26 , 27 , 28 Intriguingly, the defects in central tolerance correlate with abnormal B cell development in the thymus of NOD mice. 29 Still, the contribution of thymic B cells to T-cell tolerance in NOD mice is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…need to be considered in understanding the benefits of IL‐7‐based therapies. Quantifying the surface expression of CD5, a surrogate marker of basal T cell receptor (TCR) signal strength, Dong et al 2 . evaluated polyclonal immature and mature T cell pools in type 1 diabetes‐prone and ‐resistant mouse strains.…”
mentioning
confidence: 99%
“…The findings of Plumb et al 1 need to be considered in understanding the benefits of IL-7-based therapies. Quantifying the surface expression of CD5, a surrogate marker of basal T cell receptor (TCR) signal strength, Dong et al 2 evaluated polyclonal immature and mature T cell pools in type 1 diabetes-prone and -resistant mouse strains. While non-obese diabetic (NOD) mice had no thymic selection bias towards generating thymocytes with high-affinity TCRs for self-peptides, they were found to harbor a greater number of mature CD8 + T cells with a high CD5 expression level in their lymph nodes.…”
mentioning
confidence: 99%